Transdermal tibial nerve optogenetic stimulation targeting C-fibers - Zhou, Zhonghan; Wang, Xuesheng; Li, Xunhua; Liao, Limin (Frontiers in Physiology, 2023)
Purpose: To explore whether stimulation of C-fibers in tibial nerves can induce bladder inhibition by optogenetic transdermal illumination.Methods: Ten rats were injected with AAV2/6-hSyn-ChR2(H134R)-EYFP into the tibial nerves. Transurethral cystometry was performed 4 weeks after the virus injection. Illumination (473-nm blue light at 100 mW) was performed with the fiber positioned above the right hind paw near the ankle. The light transmission efficiency was examined with a laser power meter. The effects on cystometry were compared before and after illumination with the bladder infused with normal saline and acetic acid, respectively.Result: Upon transdermal delivery of 473-nm light at a peak power of 100 mW, the irradiance value of 0.653 mW/mm2 at the target region was detected, which is sufficient to activate opsins. The photothermal effect of 473-nm light is unremarkable. Acute inhibitory responses were not observed during stimulation regarding any of the bladder parameters; whereas, after laser illumination for 30 minutes, a statistically significant increase in bladder capacity with the bladder infused with normal saline (from 0.53±0.04 ml to 0.72±0.05 ml, P <0.001) and acetic acid (from 0.25±0.02 ml to 0.37±0.04 ml, P <0.001) was detected. A similar inhibitory response was observed with pulsed illumination at both 10Hz and 50Hz. However, illumination did not significantly influence base pressure, threshold pressure, or peak pressure.Conclusions: In this preliminary study, it can be inferred that the prolonged bladder inhibition is mediated by the stimulation of C-fibers in the tibial nerves, with no frequency-dependent characteristics. Although the 473-nm blue light has limited penetration efficacy, it is sufficient to modulate bladder functions through transdermal illumination on the superficial peripheral nervous system.